2011
DOI: 10.1074/jbc.m110.216804
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce Costunolide Synthase (CYP71BL2) and Its Homolog (CYP71BL1) from Sunflower Catalyze Distinct Regio- and Stereoselective Hydroxylations in Sesquiterpene Lactone Metabolism

Abstract: Sesquiterpene lactones (STLs) are terpenoid natural products possessing the ␥-lactone, well known for their diverse biological and medicinal activities. The occurrence of STLs is sporadic in nature, but most STLs have been isolated from plants in the Asteraceae family. Despite the implication of the ␥-lactone group in many reported bioactivities of STLs, the biosynthetic origins of the ␥-lactone ring remains elusive. Germacrene A acid (GAA) has been suggested as a central precursor of diverse STLs. The regiose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
156
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(161 citation statements)
references
References 38 publications
3
156
0
2
Order By: Relevance
“…Another simple change that could improve the yield of sesquiterpenoids in yeast is the medium. With its high stability in yeast, pESC-Leu2d can be used to reconstitute one-gene (STS alone) and three-gene (STS, P450, and CPR) biosynthetic pathways as described here and elsewhere (Nguyen et al, 2010;Ro et al, 2008), or even a four-gene (STS, two P450s, and CPR) pathway (Ikezawa et al, 2011) in both selection SC and rich YPA media. However, there is no selection pressure when YPA medium is used, and whether the transgenic yeast maintains the Leu2d plasmid or not will primarily depend on the cytotoxicity of the sesquiterpenoids endogenously produced in yeast.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another simple change that could improve the yield of sesquiterpenoids in yeast is the medium. With its high stability in yeast, pESC-Leu2d can be used to reconstitute one-gene (STS alone) and three-gene (STS, P450, and CPR) biosynthetic pathways as described here and elsewhere (Nguyen et al, 2010;Ro et al, 2008), or even a four-gene (STS, two P450s, and CPR) pathway (Ikezawa et al, 2011) in both selection SC and rich YPA media. However, there is no selection pressure when YPA medium is used, and whether the transgenic yeast maintains the Leu2d plasmid or not will primarily depend on the cytotoxicity of the sesquiterpenoids endogenously produced in yeast.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, we often reduce medium acidification (to pH 6 after the same period of culture) by adding HEPES buffer to synthetic complete (SC) medium to a final concentration of 100 mM (pH 7.0-7.5) (Ikezawa et al, 2011;Nguyen et al, 2010). Tris-HCl and phosphate buffers are found to interfere with yeast growth.…”
Section: Yeast and Plasmid Used For Sesquiterpenoid Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same group of DaeKyun Ro identified the subsequent biosynthetic steps in the routes to lettuce (Lactuca sativa) and sunflower (Helianthus annus) sesquiterpene lactones, catalysed by the founding members of the CYP71BL subfamily. It was shown that lettuce CYP71BL1 and its sunflower homologue CYP71BL2 catalyse the distinct 6a -and 8b-hydroxylation of germacrene A acid, and the authors suggest that the sunflower P450 has evolved from an ancestral 6a-hydroxylase in certain Asteraceae lineages [42] (figure 3). The first P450 function to be detected in plants was described in Echinocystis macrocalpa (Cucurbitaceae), where the successive oxidative conversion of (2)-kaur-16-ene (ent-kaurene) to the corresponding 19-alcohol, 19-aldehyde and 19-acid was observed, which required oxygen and NADPH, and showed inhibition by carbon monoxide [43].…”
Section: The Cyp71 Clan: Cradle Of Monoterpenoid and Sesquiterpenoidmentioning
confidence: 99%
“…Subsequently, key enzymes of the STL biosynthesis in Helianthus that are responsible for the transformation of farnesyldiphosphate into germacrene A (Fig. 1) and subsequent oxidation to germacrene A acid and its hydroxylated derivatives, have been identified and characterized from the transcriptome of glandular trichomes in the secretory stage (G€ opfert et al, 2005, 2009Nguyen et al, 2010;Ikezawa et al, 2011). This has now made it possible for the first time to test the conclusions from the chemical studies on H. x multiflorus with genomic sequences of genes participating in the STL synthesis of the taxa putatively involved in the origin of the hybrid.…”
Section: Introductionmentioning
confidence: 99%